PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATA KULIAH TATA HIDANG - Haryanto, Haryanto; Mulyatiningsih, Endang; E, Prihastuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The  goal  of this  research  in research & design on technology   is to produce   video  learning  media  prototype  needed   for  "Tata  Hidang"   (table set-up)  practicum   in Home  Economics,   Food  Management   study  program, Faculty  of Engineering.   The media  production   design  consists  of two parts: the subject matter  design and the video  interactive  program  design.The  subject  matter  design  and  video  interactive   program  design  in clude  matters  related  to steps  of selecting  and writing  the  goals  of the  spe cial  purpose   program   design,  selecting   and  organizing   program   contents, making  storyboard,   evaluating   storyboard   by experts  and  students,  making revision   based  on  the  results   and  comments    from  the  evaluation   of  the storyboard,   making   detailed   scripts   based   on  the  completed   storyboard, evaluating  and revising  the scripts,  making  the product  ready, taking  the pic tures  and  making   adjustments,   and  picture   editing.   Based  on  the  subject matter   and  audio-video   data,  interactive   learning   media   were   produced. There  are four steps, i.e., 1) Setting  requirements   for analysis  system,  2) De signing  software system  (algorithms,   Data Flow Diagram, flow  chart), 3) Implementing   the  Coding, and  4)  Evaluating   software system.  Black box testing was  needed  to evaluate  the product.  There  are observations   on out puts  (user  interface)  to treat parts  of the  input  regardless   of the process.  In ternal  product  validity  (by the researcher)   and  external  validity  (by expert) were tested  to insure the software quality.The result  obtained  is Video  Cassette  Display  of interactive  learningmedia  software  for "Tata  Hidang"  practicum.   The  findings  of the  research are:  1) the software was running  well  based  on internal  validity.  2) the ex ternal validity  of the software can be presented  as follows:  competence  mat ter   (81,82%),    sub-competence    coverage    (82,95%),    media   page   running (81,98%),   video  playing  (83,77%),   and  audio  hearing  (80,36%).   Based  on these  findings  the software product  for  "Tata  Hidang"  course  can  be used properly.Key words: learning media, interactive video, tata hidang